PENGARUH PENGGUNAAN APLIKASI META TERHADAP LOYALITAS KONSUMEN (STUDI KASUS KONSUMEN INDOMIE DI KOTA TANGERANG) - Sopiah Sopiah; Diah Ayu Lestari; Syamsurizal Syamsurizal (JURNAL LENTERA BISNIS, 2025)
The development of the digital era has changed the way every consumer communicates both with companies and with other consumers. The use of meta applications that continue to grow certainly has an influence on consumer habits. This study was conducted to determine the effect of using meta applications on Indomie consumer loyalty. The meta application itself is an application owned by Mark Zuckerberg which consists of Facebook, Instagram and Whatsapp. The sample in this study were consumers of Indomie products in Tangerang City, with the number of respondents used as many as 100 respondents. The sample was taken using simple random sampling technique using the Lemeshow formula. The data collection technique used in this study was to use a questionnaire distributed to respondents using a google link. The data analysis techniques used in this study are Instrument Test (Validity Test and Reliability Test), Classical Assumption Test (Normality Test, Linearity Test and Heteroscedasticity Test), Simple Linear Regression Test (Partial T Test, Correlation Coefficient Test, Simple Linear Regression Test and Determination Coefficient Test). The result of this study is that there is a significant relationship from the use of the Meta Application to Consumer Loyalty based on the t value generated is 5.966 > 1.987. Based on the Coefficient of Determination Test (R²), it is known that the R square value obtained is 0.266, which is 0.266, which means that there is an influence of 26.6%.